The Impact of Serious Games on Learning in Primary Education: A Systematic Literature Review - Arosquipa Lopez, Julissa Yeny (2024)
In recent years, serious games have gained greater relevance in the educational field due to their usefulness in the intellectual development of students. With this objective in mind, we conducted a systematic literature review on serious games in the learning of primary-school students to reveal the advantages and the disadvantages, as well as the effects of educational game strategies and in the application areas, when using the PRISMA methodology to analyse the academic progress during the last 10 years. We conducted the search, selection and analysis in different databases, such as SCOPUS, ERIC and Dimensions, and analysed 54 studies. The results showed that serious games have a positive impact on cognition; and they generate significant learning achievements. Likewise, the game-based learning strategy concentrates a high level of motivation, generated by the interest, commitment and fun to solve the activities. However, it was also noted that the competition among students to reach the highest competencies can increase the level of anxiety. In addition, inadequate methodology and teacher unfamiliarity can cause negative effects, such as apathy towards serious games. Regarding the intervention areas, a greater application was observed in mathematics, the social sciences, communication and natural sciences. On the other hand, mathematical and communicative skills are the most addressed topics.